AI Literacy and Entrepreneurial Readiness among Economics Education Students: The Mediating Role of Digital Content Creation Skills - Nurliana; Maghfirah Sari Azis (Tamaddun Life, 2026)
The rapid adoption of artificial intelligence (AI) technologies in higher education has created new opportunities for developing entrepreneurial competencies among university students. However, limited research has examined how AI Literacy contributes to Entrepreneurial Readiness and the mechanism through which this relationship occurs. This study investigates the relationships among AI Literacy, Digital Content Creation Skills, and Entrepreneurial Readiness among Economics Education students at Universitas Negeri Makassar. A quantitative survey design was employed, involving 300 undergraduate students selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings revealed that AI Literacy positively and significantly influenced Digital Content Creation Skills (β = 0.617, p < 0.001) and Entrepreneurial Readiness (β = 0.316, p < 0.001). Furthermore, Digital Content Creation Skills significantly affected Entrepreneurial Readiness (β = 0.424, p < 0.001) and partially mediated the relationship between AI Literacy and Entrepreneurial Readiness (β = 0.262, p < 0.001). The study concludes that AI Literacy represents an important antecedent of Entrepreneurial Readiness, while Digital Content Creation Skills serve as a critical mechanism linking technological competence and entrepreneurial development among university students in the digital era.